2013
DOI: 10.1089/cyber.2012.1571
|View full text |Cite
|
Sign up to set email alerts
|

Empathy Toward Virtual Humans Depicting a Known or Unknown Person Expressing Pain

Abstract: This study is about pain expressed by virtual humans and empathy in users immersed in virtual reality. It focuses on whether people feel more empathy toward the pain of a virtual human when the virtual human is a realistic representation of a known individual, as opposed to an unknown person, and if social presence is related to users' empathy toward a virtual human's pain. The 42 participants were immersed in virtual reality using a large immersive cube with images retro projected on all six faces (CAVE-Like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…As suggested by Goubert et al (2009) , closer relationships (e.g., parent–child or other family relationships) are expected to elicit faster and stronger empathic responses than stranger or adversarial relationships. In support of this interpretation, parents in this study scored children’s empathy as higher compared to self-reported measures, and there is evidence that observers’ empathic reactions to other’s physical pain are stronger when suffered by a known person compared to one unknown ( Bouchard et al, 2013 ). In concordance, Meyer et al (2013) found different activation networks in processing other’ social suffering depending on the status of the observed person, with a friend’s suffering activating affective pain regions associated with the direct experience of pain, whereas observing a stranger’s suffering activated regions associated with thinking about mental states of others.…”
Section: Discussionsupporting
confidence: 58%
“…As suggested by Goubert et al (2009) , closer relationships (e.g., parent–child or other family relationships) are expected to elicit faster and stronger empathic responses than stranger or adversarial relationships. In support of this interpretation, parents in this study scored children’s empathy as higher compared to self-reported measures, and there is evidence that observers’ empathic reactions to other’s physical pain are stronger when suffered by a known person compared to one unknown ( Bouchard et al, 2013 ). In concordance, Meyer et al (2013) found different activation networks in processing other’ social suffering depending on the status of the observed person, with a friend’s suffering activating affective pain regions associated with the direct experience of pain, whereas observing a stranger’s suffering activated regions associated with thinking about mental states of others.…”
Section: Discussionsupporting
confidence: 58%
“…Realism of virtual characters can be seen as another dimension of presence, social presence or co-presence. Social presence “reflects how users immersed in VR feel that virtual humans are really there, in the room, with them.” (p. 62) [ 73 ]. Social presence can be divided into two concepts, one focusing on the perception of embodied virtual characters and one on the social responses to the virtual characters [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, other studies showed the so called “uncanny valley” effect: the more realistic a human virtual character, the lower the tolerance for (even small) imperfections in behavioral realism. It could be that a highly realistic virtual character results in a lower social presence than a minor realistic character due to these small imperfections [ 73 75 ]. Nevertheless, it is important to note that realism of virtual characters is only one factor influencing social presence and we did not assess social presence or co-presence in a direct manner.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were paid (CAN$12/hr) after completing the experiment. The experiment took place in a CAVE-like system (Cruz-Neira, Sandin, & DeFanti, 1993) located at the UQO's cyberpsychology lab (see Bouchard et al, 2013 for a description of the hardware). CAVE (Automated Virtual Environment-the "C" refers to the allegory of the cave by the Greek philosopher Plato) is a trademarked immersive technology using stereoscopic images projected on large walls.…”
Section: Methodsmentioning
confidence: 99%
“…The heart rate was analyzed using an electrocardiogram measured using a Polar strap. The data were recorded using Thought Technology's ProComp+ program and Infinity software (http://thoughttechnology.com, see Bouchard et al, 2013 for a description of the hardware). These data were continuously transmitted and recorded wirelessly in the second half of the meeting during a base-level measuring period (2 min) and the VR immersions.…”
Section: Methodsmentioning
confidence: 99%